2009
DOI: 10.1167/9.11.28
|View full text |Cite
|
Sign up to set email alerts
|

Dissociable effects of attention and crowding on orientation averaging

Abstract: It has been proposed that visual crowding—the breakdown in recognition that occurs when objects are presented in cluttered scenes—reflects a limit imposed by visual attention. We examined this idea in the context of an orientation averaging task, having subjects judge the mean orientation of a set of oriented signal elements either in isolation, or “crowded” by nearby randomly oriented elements. In some conditions, subjects also had to perform an attentionally demanding secondary task. By measuring performance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
67
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(85 citation statements)
references
References 54 publications
17
67
1
Order By: Relevance
“…This relationship can be formalized by the additivity of variances, as in Eq. 1 (Beaudot & Mullen, 2005;Dakin, 2001;Dakin et al, 2009;Demanins et al, 1999;Heeley et al, 1997). This approach has been used successfully to estimate the internal noise and sample size for averageorientation processing (Beaudot & Mullen, 2005;Dakin, 2001;Heeley et al, 1997).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This relationship can be formalized by the additivity of variances, as in Eq. 1 (Beaudot & Mullen, 2005;Dakin, 2001;Dakin et al, 2009;Demanins et al, 1999;Heeley et al, 1997). This approach has been used successfully to estimate the internal noise and sample size for averageorientation processing (Beaudot & Mullen, 2005;Dakin, 2001;Heeley et al, 1997).…”
Section: Resultsmentioning
confidence: 99%
“…Our approach here was inspired by previous research in which variance summation modeling has been used to estimate the internal noise and efficiency (i.e., sample size) of texture discrimination mechanisms (Beaudot & Mullen, 2005;Dakin, 2001;Dakin, Bex, Cass, & Watt, 2009;Demanins, Hess, Williams, & Keeble, 1999;Heeley, Buchanan-Smith, Cromwell, & Wright, 1997). For the present case, a benefit of this approach is that, once generated, estimates of the internal noise affecting ensemble processing can be compared to behavioral estimates of the internal noise affecting individualobject processing to address the question of whether or not the internal noise for ensemble processing is lower than that for processing individual items.…”
mentioning
confidence: 99%
“…Lower-level mechanisms such as masking or lateral inhibition did not explain the crowding. Yeshurun and Rashal (2010) assessed crowding at cued versus uncued locations, finding that attention reduced the spatial extent of crowding (see also Dakin et al, 2009;Freeman & Pelli, 2007). Similarly, Strasburger (2005) concluded that impaired character recognition during crowding was caused by spatially imprecise focusing of attention.…”
Section: Discussionmentioning
confidence: 98%
“…Additionally, priming effects are fundamentally bound to attentional selection (Brascamp, Blake, & Kristjánsson, 2011;Goolsby & Suzuki, 2001). Yeshurun and Rashal (2010) reported increased identification accuracy from attentional precues for a target stimulus appearing among flankers (see also Dakin, Bex, Cass, & Watt, 2009;Freeman & Pelli, 2007;Strasburger, 2005). The cue reduced the critical distance for crowding indicating that attention reduces the spatial extent of crowding.…”
mentioning
confidence: 99%
“…Studies have rather consistently shown that crowding can be reduced by precueing the target location (Scolari, Kohnen, Barton, & Awh, 2007;Strasburger & Malania, 2013;Yeshurun & Rashal, 2010), but the reason for this is less clear. While some have found that attentional cueing reduces the critical distance between the target and distractors (Strasburger & Malania, 2013;Yeshurun & Rashal, 2010), others have found an increase in the target identification accuracy but no effect on the critical distance (Scolari et al, 2007; see also Dakin, Bex, Cass, & Watt, 2009 for similar findings with different manipulation of attention). Therefore, these studies suggest at least two possible effects of cued attention that may in turn be modified by the type of competition.…”
Section: Introductionmentioning
confidence: 89%